Culture of oral communication as a component of a positive image of a law enforcement officer - Tiahnyriadno Yevheniia (Науковий Вісник Південноукраїнського Національного Педагогічного Університету імені К. Д. Ушинського)
The relevance of the research lies in the increasing importance of public trust in law enforcement agencies amidst complex socio-political conditions and evolving technological and informational realities. Closer engagement with citizens, promoting their protection and safety, demands not only professionalism in law enforcement but also a high level of communicative skills and language culture. Consequently, understanding the impact of linguistic behavior on shaping the image of law enforcement becomes a necessary aspect for achieving effective interaction with society and ensuring harmony in the legal space. The aim of the article is to explore the role of oral communication culture in shaping the positive image of law enforcement and to identify effective communication strategies to enhance public trust in law enforcement agencies. To achieve the stated goal, the following research methods were used: projection, theoretical modeling, identification of cause-and-effect relationships, systematization, analysis of documentation, and researchers’ results on the problem under study. The content of the study reveals the main aspects of oral communication culture that significantly influence the perception of law enforcement by the public. The article analyzes language strategy and discusses communication methods that contribute to increasing trust in law enforcement agencies. In particular, the role of non-verbal communication tools, such as facial expressions and gestures, in shaping a positive perception of law enforcement is examined. The importance of using appropriate linguistic and tonal palette in communicating with the public to achieve maximum understanding and support is also thoroughly examined. The study also includes an analysis of interactive communication formats, such as public meetings, forums, and social media, and their impact on the perception of the law enforcement community. This analysis aims to identify the most effective approaches to interacting with the audience and building a positive image of law enforcement. The research findings indicate that studying and improving the oral communication culture of law enforcement officers is a crucial factor in shaping the positive image of this specialized group. Emphasizing effective use of linguistic tools and communication strategies emerges as a key element that contributes to increasing public trust in law enforcement agencies. The results of the study confirm that the right communicative strategy and cultural adaptation of language to the needs and expectations of the audience enable law enforcement officers to strengthen their image in society and increase the level of public support.